2021
DOI: 10.18632/aging.203648
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic tubular epithelial cells regulate the angiogenesis of HMEC-1 cells via mediation of Rab7/MMP-2 axis

Abstract: Renal hypoxia is associated with persisting peritubular capillary rarefaction in progression of chronic kidney disease (CKD), and this phenomenon mainly resulted from the dysregulated angiogenesis. Rab7 is known to be involved in renal hypoxia. However, the mechanism by which Rab7 regulates the renal hypoxia remains unclear. Protein expression was detected by western blot. Cell proliferation was detected by EdU staining. Cell migration was tested by transwell assay. Rab7 was upregulated in HK-2 cells under hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Studies have found that ECs produce VEGF, matrix metallopeptidase 2 (MMP-2), and chemokines to promote neovascularization during acute injury in the lung, liver, and kidney [ 16 , 38 ]. Renal tubular epithelial cells can regulate the angiogenesis function of ECs by upregulating Rab7 gene expression, and mediating the expression of Rab7/MMP-2/VEGF axis [39] . However, when organ damage persists, ECs are aberrantly activated to produce pro-fibrotic mediators such as TGF-β, CCL, and FGF, which induce fibroblast proliferation and production of the ECM [ 16 , 38 , [40] , [41] , [42] ].…”
Section: Changes To Cellular Signaling Pathways During Organ Fibrosis...mentioning
confidence: 99%
“…Studies have found that ECs produce VEGF, matrix metallopeptidase 2 (MMP-2), and chemokines to promote neovascularization during acute injury in the lung, liver, and kidney [ 16 , 38 ]. Renal tubular epithelial cells can regulate the angiogenesis function of ECs by upregulating Rab7 gene expression, and mediating the expression of Rab7/MMP-2/VEGF axis [39] . However, when organ damage persists, ECs are aberrantly activated to produce pro-fibrotic mediators such as TGF-β, CCL, and FGF, which induce fibroblast proliferation and production of the ECM [ 16 , 38 , [40] , [41] , [42] ].…”
Section: Changes To Cellular Signaling Pathways During Organ Fibrosis...mentioning
confidence: 99%
“…Before induction of hypoxia in HMEC-1 cells, the medium was replaced with a sugar-free and serum-free medium to simulate nutrient deprivation. In addition, the HMEC-1 cells were placed in a hypoxic chamber (1% O2, 5% CO2, and 94% N2) for further 2 h culture [ 20 ].…”
Section: Methodsmentioning
confidence: 99%